Cross-layer design and implementation of cognitve radio system - Mohiuddin, Ibrahim Bin; Anis, Nawshin; Ahmed, Saraf Wamia; Anan, Zaki (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.